Study on the quantitative characterrs in immature clones of Hevea brasiliensis by genetic methods - Hu JianGuang; Lin Sheng; Zhang GenFa (Acta Agronomica Sinica, 1995)
For 13 characters in 16 clones, broad-sense heritability estimates, correlated heritabilities between the characters, genotypic and phenotypic coefficients of variation, and relative and absolute genetic advance were analysed and compared. The relative efficiency of indirect selection for test-tapping yield through other characters was estimated, and selection indexes for test-tapping yield were established on the basis of calculations of genetic correlations. The 3 characters judged the most important for selecting good seedlings were reference angle, plugging index and yield index, and the best selection index was the eleventh, which comprised these 3 characters and 2 others (specific leaf weight and primary bark thickness).
Source Year: 1996
Keywords: Genetic correlation; Hevea brasiliensis; Immature clones